Population pharmacokinetic-pharmacodynamic model of dexmedetomidine in elderly patients undergoing sedation after abdominal aortic surgery - Ber, Justyna Alicja; Bienert, Agnieszka; Sobczyński, Paweł; Nowicka, Małgorzata; Żurański, Łukasz; Hołysz, Marcin; Grześkowiak, Edmund; Wiczling, Paweł (Journal of Medical Science, 2023)
Background. Dexmedetomidine (DEX) is a widely used sedative agent for treating post-surgery patients. It also acts on hemodynamic parameters like heart rate or cardiac output. This study aimed to develop a pharmacokinetic-pharmacodynamic (PK/PD) model of DEX using bispectral index (BIS) and cardiac output (CO) as a response.Methodology and results. 21 mechanically ventilated elderly cardiac patients undergoing abdominal aortic surgery were enrolled in the study. DEX was given to maintain moderate or deep sedation. Genotypes of ADR2A*55 were identified using real-time PCR-HRM. Data were analyzed using nonlinear mixed-effect modelling. A two-compartment model described DEX pharmacokinetics. The sigmoid Emax and linear models were used to describe BIS and CO measurements. The typical value of EC50 for DEX effects on BIS was 3.62 ng/ml, and the slope between CO and DEX concentrations was 0.819 (L/min)/(ng/ml). We were unable to show the effects of considered covariates on DEX pharmacodynamics.Conclusions. WE proposed the PK/PD model of DEX to understand better the BIS and CO changes observed after surgery. The measured CI values were in the reference range showing that the used doses of DEX ensured stable cardiac function in the studied patients.
Keywords: pharmacodynamics; dexmedetomidine; intensive care units; geriatrics; analgosedation